Zeolite-based hemostat QuikClot releases calcium into blood and promotes blood coagulation in vitro - Li, Jing; Cao, Wei; Lv, Xiao-xing; Jiang, Li; Li, Yue-jun; Li, Wang-zhou; Chen, Shao-zong; Li, Xue-yong (Acta pharmacologica Sinica, 2013)
Aim: To examine the changes in electrolyte concentrations after addition of zeolite-based hemostat QuikClot in blood and the effects of zeolite on blood coagulation in vitro . Methods: Fresh blood was taken from healthy adult volunteers and sheep, and the electrolyte concentrations in blood were measured using a blood electrolyte analyzer. Zeolite Saline Solution (ZSS) was prepared by addition of 2 g zeolite to 0.9% NaCl solution (4, 8, or 16 mL). The electrolytes in ZSS were measured using inductively coupled plasma atomic emission spectroscopy. The prothrombin time (PT) and activated partial thromboplastin time (APTT) of blood were measured using the test tube method. The activated clotting time (ACT) and clotting rate (CR) of blood were measured with Sonoclot Coagulation and Platelet Function Analyzer. Results: Addition of zeolite (50 and 100 mg) in 2 mL human blood significantly increased Ca 2+ concentration, while Na + and K + concentrations were significantly decreased. Addition of zeolite (50 and 100 mg) in 0.9% NaCl solution (2 mL) caused similar changes in Ca 2+ and Na + concentrations. Si 4+ (0.2434 g/L) and Al 3+ (0.2575 g/L) were detected in ZSS (2 g/8 mL). Addition of ZSS in sheep blood shortened APTT in a concentration dependent manner, without changing PT. ZSS or aqueous solution of CaCl 2 that contained Ca 2+ concentration identical to that of ZSS significantly shortened ACT in human blood without significantly changing CR, and the effect of ZSS on ACT was not significantly different from that of CaCl 2 . Conclusion: Zeolite releases Ca 2+ into blood, thus accelerating the intrinsic pathway of blood coagulation and shortening the clot formation time.